Pengaruh Literasi Keuangan, Inklusi Keuangan Dan Financial Technology Terhadap Keputusan Investasi Nasabah Bank Mandiri Cabang Jakarta Kebon Jeruk Perjuangan - Murdiyati, Dwi Mei; Rizkita, Citra (DAS Institute, 2025)
This study aims to analyze the factors that are suspected of influencing customer investment decisions, especially at Bank Mandiri Jakarta Kebon Jeruk Perjuangan. The factors in question are financial literacy, financial inclusion, and financial technology. The type of research used is quantitative, with the data used in the form of secondary data. The sample determination used the purposive sampling method with a total of 89 respondents who will be used for this study. The analysis method used is multiple linear regression. The results of the study show that the three independent variables, namely financial literacy (X1), financial inclusion (X2), and financial technology (X3) have a simultaneous effect on investment decisions (Y) based on the F test, in the ANOVA table above, the significance value (Sig) can be seen less than 0.05 and f count> f table, 252,905> 2.71. While the partial hypothesis test (T test) states that the three independent variables also influence investment decisions.